Ytterbium(iii)-catalyzed three-component reactions: synthesis of 4-organoselenium-quinolines. (11th August 2017) - de Oliveira, Isadora M.; Vasconcelos, Stanley S. N.; Barbeiro, Cristiane S.; Correra, Thiago C.; Shamim, Anwar; Pimenta, Daniel C.; Caracelli, Ignez; Zukerman-Schpector, Julio; Stefani, Hélio A.; Manarin, Flávia
Abstract : 4-Organoselenium-quinolines were synthesized via model multi-component Povarov reactions between p -anisidine, ethyl glyoxylate and ethynyl(phenyl)selane. Abstract : 4-Organoselenium-quinolines were synthesized via model multi-component Povarov (MCR) reactions between p -anisidine, ethyl glyoxylate and ethynyl(phenyl)selane, catalyzed by the Lewis acid Yb(OTf)3, with yields ranging from moderate to good. This method is advantageous in that there is no requirement for an oxidant and that the reaction has a wide scope. These 4-organoselenium-quinolines allowed access to 4-alkynyl-quinolines, which were synthesized via copper free Sonogashira cross-coupling reactions catalyzed by a new palladium catalyst that employs an oxazoline derivative as a ligand. A plausible mechanism was proposed based on HRMS studies.